Responses of soil microorganisms to simulated climate change in desert grassland in northern China. Issue 4 (3rd March 2022) - Zhang, Yi; Xie, Ying-Zhong; Ma, Hong-Bin; Zhang, Juan; Jing, Le; Wang, Yu-Tao; Li, Jian-Ping
Abstract: The study evaluates how simulated climate change affects microorganism communities in the desert grassland of Ningxia Autonomous Region, China. It explores the soil microorganism community and relationships among the soil microorganism community, chemical properties, soil respiration (SR), and plant biomass under climate change. We established a field experiment with five levels of rainfall using rainout shelters and two levels of temperature by the Open-Top Chamber (OTC). The results show that in fungal communities, normal precipitation will promote the number and base number of valid sequences the most, and R66 will significantly promote the mean length of the valid sequence. In the bacterial communities, the interaction of increasing temperature and R133 will promote the number of valid sequences and R166 will promote the length of valid sequences. Neither rainfall nor rising temperature promotes not only the soil community α-diversity but also the soil microorganism community β-diversity. Soil microorganism communities show resistance to rainfall. SR will limit the soil microorganism diversity. Soil organic carbon (SOC), soil total nitrogen (STN), and soil total phosphorus (STP) will promote soil microorganism abundance (SMA) and soil microorganism diversity (SMS). Aboveground living biomass (ALB) and soil temperature (ST) will promote soil α-diversity, whereas the effect of root biomass (RB) on the soil α-diversity is the opposite. HIGHLIGHTS: Climate change effects on microorganism communities and relationships in Ningxia Autonomous region are examined. Field experiments used five levels of rainfall and two of temperature. Results show normal precipitation best promotes the number and base number of valid sequences. R66 was found to significantly promote the number of valid sequences.